Predictors of Pain and Function Before Knee Arthroscopy. Issue 5 (13th May 2019) - ,; Bessette, Matthew C.; Westermann, Robert W.; Davis, Alan; Farrow, Lutul; Hagen, Mia S.; Miniaci, Anthony; Nickodem, Robert; Parker, Richard; Rosneck, James; Saluan, Paul; Spindler, Kurt P.; et al.
Background: Patient-reported outcome measures are commonly used to measure knee pain and functional impairment. When structural abnormality is identified on examination and imaging, arthroscopic partial meniscectomy and chondroplasty are commonly indicated for treatment in the setting of pain and decreased function. Purpose: To evaluate the relationship between patient characteristics, mental health, intraoperative findings, and patient-reported outcome measures at the time of knee arthroscopy. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Between February 2015 and October 2016, patients aged 40 years and older who were undergoing routine knee arthroscopy for meniscal and cartilage abnormality, without reconstructive or restorative procedures, were prospectively enrolled in this study. Routine demographic information was collected, and the Knee injury and Osteoarthritis Outcome Score (KOOS) Pain, Quality of Life (QoL), and Physical Function Short Form (PS) subscales and the mental and physical component subscales of the Veterans RAND 12-Item Health Survey (VR-12 MCS and VR-12 PCS) were administered preoperatively on the day of surgery. Intraoperative findings were collected in a standardized format. Patient demographics, intraoperative findings, and the VR-12 MCS were used as predictor values, and a multivariate analysis was conducted to assess for relationships with the KOOS and VR-12 as dependent variables. Results: Of 661 eligible patients, baseline patient-reported outcomes and surgical data were used for 638 patients (97%). Lower scores on both subscales of the VR-12 were predicted by female sex, positive smoking history, fewer years of education, and higher body mass index (BMI). All KOOS subscales were negatively affected by lower VR-12 MCS scores, female sex, lower education level, and higher BMI in a statistically meaningful way. Positive smoking history was associated with worse scores on the KOOS-PS. Abnormal synovial status was associated with worse KOOS-Pain. Conclusion: The demographic factors of sex, smoking status, BMI, and education level had an overwhelming impact on preoperative KOOS and VR-12 scores. Of interest, mental health as assessed by the VR-12 MCS was also a consistent predictor of KOOS scores. The only intraoperative finding with a significant association was abnormal synovial status and its effect on KOOS-Pain scores.